2011
DOI: 10.1007/s10529-011-0577-9
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of survivin and cyclin D1 in CHO cells confers apoptosis resistance and enhances growth in serum-free suspension culture

Abstract: To optimize Chinese hamster ovary (CHO) cell culture to recombinant protein therapeutic production, we stably overexpressed survivin and cyclin D1 in three CHO DG44-derived cell lines. The modifications conferred increases of 56-94% in S-phase fractions and decreases of 33-43% in early-stage apoptosis fractions. Clone 6.3, which expressed the highest levels of survivin and cyclin D1, reached significantly greater cell densities in suspension (2.7 × 10(6) cells/ml) following serum deprivation. Nude mice inocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…It was reported that the over-expression of Survivin can help cancer cells to pass G2-M checkpoint [37], [38]. At the same time, Survivin possesses a capability to upregulate the expression of Cyclin D1 and ensures cancer cells to pass G1-S checkpoint fluently and obtain an ability of persistent proliferation [38], [39].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the over-expression of Survivin can help cancer cells to pass G2-M checkpoint [37], [38]. At the same time, Survivin possesses a capability to upregulate the expression of Cyclin D1 and ensures cancer cells to pass G1-S checkpoint fluently and obtain an ability of persistent proliferation [38], [39].…”
Section: Discussionmentioning
confidence: 99%
“…Survivin is a small, versatile, structurally unique member of the inhibitor of apoptosis (IAP) protein family in mammalian cells 10) that protects cells from caspase-dependent and caspase-independent apoptosis when overexpressed. 8,11) Compared to constitutive overexpression, inducible expression of survivin in CHO cells generates more controllable, flexible CHO cell lines, whose anti-apoptosis performance can be regulated. Furthermore, inducible expression rules out the possible site effect originating in different integration loci of the expression vectors, which makes it more suitable for gene function study.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR was performed as previously described. 8) Western blotting. Whole-cell lysates were prepared as described in reference 8.…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcriptase (RT)-PCR was performed as previously described, 22 using HBx primers (forward, 5′-gctgctaggctgtgctgc-3′; reverse, 5′-atgcctcaaggtcggtcgt-3′). β-Actin primers (forward, 5′-caaccgcgagaagatgac-3′; reverse, 5′-agggtacatggtggtgcc-3′) were used as an internal control.…”
Section: Real-time Pcrmentioning
confidence: 99%